Implikasi Pendidikan dari Q.S An-Najm Ayat 5-6 tentang Konsep Pengajaran Jibril terhadap Upaya Peningkatan Profesionalisme Guru - Reni Risma Nursolihat; Dedih Surana; Dinar Nur Inten (UNISBA Press, 2023)
Abstract. Indonesian education currently has a fairly poor quality when compared to several countries in the world. One of the problems with Indonesian education today is that there are still incompetent teachers. Because in improving the quality of education and professionalism of teachers, teachers must have competence. So every teacher is required to continue to strive to improve teacher professionalism. The purpose of this study was to analyze: 1) opinion of mufassirin related to Q.s. An-Najm verses 5-6, 2) the essence contained in Q.s. An-Najm verses 5-6, 3) the opinion of education experts about teacher professionalism, 4) the educational implications contained in Q.s. An-Najm verses 5-6 concerning the concept of Jibril's teaching towards efforts to increase teacher professionalism. This study uses a qualitative approach to the type of library research (library research). The method of interpretation uses the tahlili, muqoron and tarbawi methods.The result of this study reveal in the Q.s An-Najm verse 5-6 that teachers, in order to make afforts to educate their professionalism as done bt the angel Jibril a.s. regarding the teaching of revelation to the Prophet Muhammad saw. Are carried out very well and correctly so that he teaching reaches mankind. Professional teachers are teachers who have the competence so that the delivery of learning material is carried out properly and correctly. This is to support the task of professionalism.The educational implications contained in the Qur'an Surah An-Najm verses 5-6 are firstly, the delivery of learning materials properly, correctly and beautiful. Both, understanding and application of teachear competence in depth. Thirdly, a teacher must have spiritual strength. Fourth, a teachers must have physical strength.Abstrak. Pendidikan Indonesia saat ini memiliki mutu yang cukup buruk jika dibandingkan dengan beberapa negara di dunia. Salah satu permasalahan pendidikan Indonesia sekarang, yaitu masih terdapat guru yang belum kompeten. Sebab dalam meningkatkan kualitas pendidikan serta profesionalitas guru, harus memiliki kompetensi guru. Maka setiap guru dituntut untuk terus berupaya dalam meningkatkan profesionalisme guru. Tujuan penelitian ini untuk menganalisis: 1) pendapat mufassirin terkait dengan Q.s. An-Najm ayat 5-6, 2) esensi yang terkandung dalam Q.s. An-Najm ayat 5-6, 3) pendapat para ahli pendidikan tentang profesionalisme guru, 4) implikais pendidikan yang terkandung dalam Q.s An-Najm ayat 5-6 tentang konsep pengajaran Jibril terhadap upaya peningkatan profesionalisme guru. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Adapun metode penafsirannya menggunakan metode tahlili, muqoron dan tarbawi.Hasil dari penelitian ini mengungkapkan di dalam Q.s An-Najm ayat 5-6 bahwa guru, agar melakukan upaya peningkatan profesionalismenya seperti yang dilakukan oleh malaikat Jibril a.s. mengenai pengajaran wahyu kepada Nabi Muhammad saw. dilakukan dengan sangat baik dan benar sehingga pengajaran tersebut sampai kepada umat manusia. Guru yang profesional yaitu guru yang memiliki kompetensi agar penyampaian materi pembelajaran dilakukan dengan baik dan benar. Hal ini untuk menunjang tugas profesionalisnya.Implikasi pendidikan yang terdapat dalam Al-Qur’an surat An-Najm ayat 5-6 adalah pertama, penyampaian materi pembelajaran dengan baik, benar, dan indah. Kedua, pemahaman serta pengaplikasian kompetensi guru secara mendalam. Ketiga, seorang guru harus memiliki kekuatan secara rohani. Keempat, seorang guru harus mempunyai kekuatan secara jasmani.